Prevalence of intimate partner violence and associated factors amongst women attending antenatal care at Outapi primary health care facility, Namibia: a descriptive survey - Bikinesi, Leonard Timothy (Stellenbosch : Stellenbosch University, 2017)
Thesis (MFamMed)--Stellenbosch University, 2017.